Extrahepatic abdominal hydatid disease caused by Echinococcus granulosus: Imaging findings - (:unkn) unknown (AMER ROENTGEN RAY SOC, 2007)
OBJECTIVE. The classical findings in hydatid disease caused by Echinococcus granulosus with liver or lung involvement are well known. However, diagnosing hydatid disease at unusual locations may be challenging because of variable imaging appearances depending on the host reaction. The purpose of this pictorial essay is to review the sonographic, CT, and MRI features of extrahepatic abdominal hydatid disease including intraperitoneum, retroperitoneum, diaphragma, bone, and soft tissue of the abdomen. CONCLUSION. Extrahepatic abdominal hydatid lesions have nearly identical imaging features, including the presence of cyst wall calcification, daughter cysts, and membrane detachment. The combinations of radiologic and serologic tests especially in patients living in the endemic areas contribute to the diagnosis. Despite their rarity, being familiar with the spectrum of radiologic findings in these unusual sites is helpful to improve diagnostic accuracy.
Keywords: abdominal imaging; CT; extrahepatic hydatid disease; MRI; sonography